Deep eutectic solvent and additive manufacturing: sustainable approaches for the development of electrochemical sensors - Augusto, Karen Kenlderi de Lima (Universidade Federal de São Carlos, 2025)
The thesis investigated the use of hydrophobic deep eutectic solvents and additive manufacturing to develop sustainable electrochemical sensors, aligning with the principles of green chemistry. To do this, an HDES composed of decanoic acid and tetrabutylammonium bromide was studied and synthesised, characterised using techniques such as differential scanning calorimetry, infrared spectroscopy, and nuclear magnetic resonance. For the first time, the synthesis of HDES was optimised using in situ infrared spectroscopy, reducing the preparation time to less than five minutes at 80 ºC, thereby contributing to energy savings and the environmental feasibility of the process. The application of HDES was explored in the modification of electrodes for electrochemical sensors aimed at detecting compounds of environmental and medical interest. One of the key studies involved modifying glassy carbon electrodes with HDES and carbon nanohorns for serotonin detection. The modified electrode (DecA(5mg)-CNH/GCE) exhibited significant improvements in electrochemical performance due to the synergistic effect between HDES and CNH, promoting greater coverage of carbon nanoparticles and a homogeneous surface, facilitating electron transfer in serotonin oxidation. Another study employed HDES in the modification of carbon paste electrodes for the detection of diuron, a widely used herbicide. The voltammetric method developed demonstrated good reproducibility and effective recovery of diuron in water samples, highlighting the sensor's applicability for environmental monitoring. Beyond conventional electrodes, the research explored additive manufacturing to develop sustainable conductive filaments. One of the filaments was composed of carbon black, graphite functionalised with silver nanoparticles (AgNPs), castor oil, and recycled PLA. The AgNPs were synthesised in an eco-friendly manner without reducing agents, using the graphite itself as the forming material, and characterised by SEM/EDX, XRD, and XPS. Electrodes printed from this material demonstrated high efficiency in cadmium detection in water, with a detection limit below the global regulatory threshold of 5 µg L⁻1, making them viable for environmental analyses. Another innovative approach was the pioneering development of a filament containing HDES. In this study, the HDES was combined with carbon black, cellulose, recycled PLA, and castor oil. Electrodes printed from this filament exhibited electrochemical improvements compared to filaments developed without HDES and a commercial filament. As proof of functionality, the electrodes were applied in the detection of acetaminophen in water, demonstrating their analytical efficiency and sustainability. This work highlighted the potential of combining HDES and additive manufacturing to create environmentally friendly electrochemical sensors, driving advancements in sustainable analytical chemistry. Additionally, it reinforces the feasibility of using simple and green materials in the development of new sensors, aligning with the principles of green chemistry and the United Nations’ Sustainable Development Goals.
Solvente eutético profundo e manufatura aditiva: abordagens sustentáveis ​​para o desenvolvimento de sensores eletroquímicos
Keywords: Sustentabilidade; Solvente eutético profundo hidrofóbico; Manufatura aditiva; Impressão 3D; Química verde; Sensores eletroquímicos; Desenvolvimento sustentável; Sustainability; Hydrophobic deep eutectic solvent; Additive manufacturing; 3D printing; Green chemistry; Electrochemical sensors; Sustainable development; CIENCIAS EXATAS E DA TERRA::QUIMICA